2005
DOI: 10.1207/s15328023top3201_7
|View full text |Cite
|
Sign up to set email alerts
|

Elaborations of Introductory Psychology Terms: Effects on Test Performance and Subjective Ratings

Abstract: Undergraduate students participated in an experiment designed to evaluate different types of elaborations on definitions of 16 psychology terms. First, participants received booklets presenting the definition of each term, followed by 1 of several elaborations: an example, a mnemonic, a paraphrase, or a repeated definition (the nonelaborating control condition). Then students received a multiple-choice test consisting of questions both on the definitions and on novel examples of the terms. Compared to repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Recent articles in Teaching of Psychology (Balch, 2005;Bloom & Lamkin, 2006;Lakin, Morris, Giesler, & Vosmik, 2007;Stalder, 2005) have endorsed the classroom use of various mnemonic techniques, such as the keyword method and acronyms. More broadly, a decidedly positive research literature exists regarding such strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent articles in Teaching of Psychology (Balch, 2005;Bloom & Lamkin, 2006;Lakin, Morris, Giesler, & Vosmik, 2007;Stalder, 2005) have endorsed the classroom use of various mnemonic techniques, such as the keyword method and acronyms. More broadly, a decidedly positive research literature exists regarding such strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent articles in Teaching of Psychology (Balch, 2005;Bloom & Lamkin, 2006;Lakin, Morris, Giesler, & Vosmik, 2007;Stalder, 2005) have endorsed the classroom use of various mnemonic techniques, such as the keyword method and acronyms. More broadly, a decidedly positive research literature exists regarding such strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, if Balch's (2005) finding of equal memory benefit for instructor-provided keyword mnemonics and examples was extended to self-created materials, then the generation effect should be equivalent for both types of study techniques.…”
mentioning
confidence: 99%
“…Their results, which built on those of Levin (1998, 2008), uniformly and strongly supported the advantages of the keyword mnemonic in a variety of time delays and recall contexts. Balch (2005) took a slightly different approach to investigating the keyword mnemonic, by having his introduction to psychology students encode various psychology terms (including brain terms) using examples, keyword mnemonics, paraphrases, or twice-repeated definitions (in the control condition), all provided by the instructor. Results showed that performance on definitional and applied multiple choice questions were equivalent for the example and keyword conditions and that these levels were significantly higher than the control condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation